Trumping religion : the new Christian right, the free speech clause, and the courts - Brown, Steven Preston (Book collections on Project MUSE., 2002)
The first scholarly treatment of the strategies employed by the New Christian Right in litigating cases regarding religion. Trumping Religion provides a detailed analysis of the five major public-interest law firms that have litigated religion cases in the federal courts between 1980 and 2000. Allied with several highly vocal, evangelical ministries, such as those of Jerry Falwell and Pat Robinson, these legal organizations argue that religious expression is a form of protected speech and thereby gain a greater latitude of interpretation in the courts. The long-term agenda of the New Christian.